2017
DOI: 10.1155/2017/4025964
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Water Resources over the Kotmale Reservoir in Sri Lanka Using ENSO Phases

Abstract: In this study, the El Nino Southern Oscillation (ENSO) phase index is used for water management over the Kotmale reservoir in Sri Lanka. Daily rainfall data of 9 stations over the Kotmale catchment during 1960-2005 June-September (JJAS) season is investigated over the Kotmale catchment. The ENSO phases are identified based on the 0.5 ∘ C sea surface temperature (SST) anomaly over Nino 3 region. The study has brought out few stations showing increasing and a few decreasing seasonal rainfall trends for JJAS seas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…This shows that there is a significantly positive connection between IOD and droughts in the Mullaitivu district. The finding is consistent with previous studies (Suppaiah, 1996;Chandrasekara et al, 2017;Jayawardene et al, 2015;Zubair, 2002), which showed positive correlations between the rainfall variability and the IOD in Sri Lanka.…”
Section: Correlation Between Iod and Drought In Mullaitivu Districtsupporting
confidence: 93%
See 1 more Smart Citation
“…This shows that there is a significantly positive connection between IOD and droughts in the Mullaitivu district. The finding is consistent with previous studies (Suppaiah, 1996;Chandrasekara et al, 2017;Jayawardene et al, 2015;Zubair, 2002), which showed positive correlations between the rainfall variability and the IOD in Sri Lanka.…”
Section: Correlation Between Iod and Drought In Mullaitivu Districtsupporting
confidence: 93%
“…This is similar to El Nino Southern Oscillation (ENSO), which influences countries' air and sea temperature conditions (Shelton & Lin, 2019). Recent findings revealed that the IOD is the leading cause of the extreme dry spell conditions in Sri Lanka (Chandrasekara et al, 2017). Anomalies of the atmospheric temperature and the increases in surface temperature induce dry situations in Northwestern, Northern, Eastern, Southeastern, and North Central provinces of Sri Lanka (Peries, 2006).…”
Section: Introductionmentioning
confidence: 88%
“…Often, climate change first appears as an increase of intensity and frequency of extreme weather events [4], and therefore, it is essential for historical trend assessments to include extreme events. Sri Lanka is affected by both floods and severe droughts, and the impacts of both have intensified in recent years [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…e study in [30] studied ways to increase power generation in hydropower plants by controlling soil erosion, reservoir siltation in Uma Oya basin, which is regarded to be one of the most important catchments in Sri Lanka. e study in [31] studied inflows in the Kotmale reservoir using El Nino Southern Oscillation (ENSO) phase index for the period of 1960 to 2005 and found that the inflows to the reservoir have decreased, altering hydropower production and irrigation plan. e study in [32] using GCMs based studies (mainly rainfall) projected that the future production capacity of the hydropower plants in the Mahaweli basin would increase as a result of an increase in consecutive wet days, decrease in consecutive dry days, and increase in annual total precipitation.…”
Section: Sri Lanka and Its Hydropower Generationmentioning
confidence: 99%